Recurrent depression relates to worse outcomes than single episode depression among Hispanic adolescents with diabetes - Keiliany Rivera-Santiago; Eduardo Cumba-Aviles; Demivette Gómez-Rivera (Health Psychology Report, 2023)
Background Adolescents with type 1 diabetes (T1D) are at increased risk for depression. A history of recurrent depression (HRD) may relate to worse health outcomes than single-episode depression. However, no study has explored this issue among T1D adolescents.